La estimulación cognitiva como estrategia psicopedagógica para mejorar las dificultades atencionales en un estudiante con Trastorno por déficit de atención de noveno año de la Unidad Educativa Emiliano Ortega Espinoza, 2023 - Aveiga Bustamante, Anahi Desiree (2023)
The objective of the curricular integration work was to implement cognitive stimulation as a psycho-pedagogical strategy to improve the attentional difficulties of a ninth grade student with ADD at the Emiliano Ortega Espinoza Educational Unit, 2023, the research had a qualitative approach, descriptive, cross-sectional, case study method and the techniques and instruments used were the psycho-pedagogical record, observation sheet, checklist, Before the intervention, the student presented problems in selective and sustained attention, which made it difficult for him to concentrate in the accomplishment of specific tasks or activities, affecting his ability to follow instructions and participate effectively in the educational environment, so it is evident the need to strengthen this cognitive process in order to improve the student's academic performance. Based on these results, cognitive stimulation was considered as a psycho- pedagogical strategy to face these difficulties, for which a guide was designed in accordance with the symptomatological characteristics of the study object of the research, which evaluated after the intervention with the checklist shows a significant progress in the attentional area. Therefore, it is essential to highlight the usefulness of cognitive stimulation for the improvement of the areas of selective and sustained attention, which is why the application of the cognitive stimulation guide resulting from this research is recommended as a psycho-pedagogical strategy to improve the attentional difficulties of the students.